Movement demands of elite rugby league players during Australian National Rugby League and European Super League matches - Twist, C.; Highton, J.; Waldron, M.; Edwards, E.; Austin, D.; Gabbett, T. J. (International Journal of Sports Physiology and Performance, 2014)
Purpose: This study compared the movement demands of players competing in matches from the elite Australian and European rugby league competitions. Methods: Global positioning system devices were used to measure 192 performances of forwards, adjustables, and outside backs during National Rugby League (NRL; n = 88) and European Super League (SL; n = 104) matches. Total and relative distances covered overall and at low (0-3.5 m/s), moderate (3.6-5 m/s), and high (>5 m/s) speeds were measured alongside changes in movement variables across the early, middle, and late phases of the season. Results: The relative distance covered in SL matches (95.8 ± 18.6 m/min) was significantly greater (P < .05) than in NRL matches (90.2 ± 8.3 m/min). Relative low-speed activity (70.3 ± 4.9 m/min vs 75.5 ± 18.9 m/min) and moderate-speed running (12.5 ± 3.3 m m/min vs 14.2 ± 3.8 m/min) were highest (P < .05) in the SL matches, and relative high-speed distance was greater (P < .05) during NRL matches (7.8 ± 2.1 m/min vs 6.1 ± 1.7 m/min). Conclusions: NRL players have better maintenance of high-speed running between the first and second halves of matches and perform less low- and moderate-speed activity, indicating that the NRL provides a higher standard of rugby league competition than the SL.